English Language Teaching in Islamic Boarding School: Navigating the Digital Revolution - Putri, Nadya Aulia; Anugerahwati, Mirjam; Febrianti, Yusnita (Institut Agama Islam Negeri Ponorogo, 2025)
Teaching English in Islamic boarding schools or traditional Islamic educational institutions in Indonesia faces significant challenges due to technological developments. In recent years, technology has changed how people learn, communicate, and interact. This study aims to investigate how English teachers teach English in the digital era when Islamic boarding school regulations prohibit students from bringing gadgets. Qualitative study was used in this study by using interview and observations as data collection technique. The findings of this study revealed that the educational pattern at pesantren fulfilled the characteristics of a modern pesantren with formal and informal education system. English teachers do not refuse the existence of technology but do not use it as the primary method of learning in the classroom. The learning method is still based on teacher-centered and lecture-based learning methods. Some challenges in teaching English are traditional learning methods, monotonous classroom atmosphere, lack of teacher competence, and lack of teaching sources. The conclusion emphasizes the need for teacher training, improved teaching methods, and teaching sources.